The Coming-of-Age Story: A Theoretical Understanding - Institute of Creative Writing, UP-LIKHAAN (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 2 (2024): THE SUMMER OF GROWING UP: STORIES OF CHILDHOOD. Reading and Writing the Philippine Coming-of-Age Story ( A Special Issue of the Likhaan: The Journal of Contemporary Philippine Literature), 2024)
.